WHOLE-EXOME SEQUENCING REVEALS PATHOGENIC SIRT1 VARIANT IN BRAIN ARTERIOVENOUS MALFORMATION: A CASE REPORT - Mukhtarova, Kymbat; Zholdybayeva, Elena; Kairov, Ulykbek; Akhmetollayev, Ilyas; Nurimanov, Chingiz; Kulmirzayev, Marat; Makhambetov, Yerbol; Ramankulov, Yerlan (Genes, 2022)
Arteriovenous malformations of the brain (bAVMs) are plexuses of pathological arteries and veins that lack a normal capillary system between them. Intracranial hemorrhage (hemorrhagic stroke) is the most frequent clinical manifestation of AVM, leading to lethal outcomes that are especially high among children and young people. Recently, high-throughput genome sequencing methods have made a notable contribution to the research progress in this subject. In particular, whole-exome sequencing (WES) methods allow the identification of novel mutations. However, the genetic mechanism causing AVM is still unclear. Therefore, the aim of this study was to investigate the potential genetic mechanism underlying AVM.We analyzed the WES data of blood and tissue samples of a 30-year-old Central Asian male diagnosed with AVM. We identified 54 polymorphisms in 43 genes. After in-silica overrepresentation enrichment analysis of the polymorphisms, the SIRT1 gene variant (g.67884831C>T) indicated a possible molecular mechanism of bAVM. Further studies are required to evaluate the functional impact of SIRT1 g.67884831C>T, which may warrant further replication and biological investigations related to sporadic bAVM.
Keywords: Type of access: Open Access; brain arteriovenous malformation; whole exome sequencing; case study; SNP; somatic mutations